News Translation From English to Indonesian - Haru Deliana Dewi (Journal of English Language and Culture, 2017)
This research paper focuses on news translation from English to Indonesian and attempts to discover the translation methods, procedures, and strategies applied in this type of translation. The material used was obtained from a US news website as the source text and from an Indonesian newspaper as the target text. The analysis started from small differences to big and obvious differences. The faithful translation was made by me to show how the translator of the target text applies translation methods, procedures, and strategies. The results of this analysis reveal that free translation has been applied in this news translation. Keywords: news translation, from English to Indonesian, translation methods, procedures, and strategies, free translation